2020
DOI: 10.1055/a-1012-1811
|View full text |Cite
|
Sign up to set email alerts
|

Cap-fitted endoscopic mucosal resection of ≥ 20 mm colon flat lesions followed by argon plasma coagulation results in a low adenoma recurrence rate

Abstract: Background and study aims Endoscopic mucosal resection (EMR) is increasingly used for the treatment of large colonic polyps (≥ 20 mm). A drawback of EMR is local adenoma recurrence. Therefore, we studied the impact of argon plasma coagulation (APC) of the EMR edge on local adenoma recurrence. Patients and methods This was a retrospective study of patients with laterally spreading tumors (LST) ≥ 20 mm, who underwent EMR from January 2009 to August 2018 and follow-up endoscopic assessment. A cap-fitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In order to reduce recurrence rates, APC is applied to the entire margin of the resection site leaving a white touch indicating the coagulated tissue. In line with our findings, a large retrospective multicenter cohort study from 2019 treating 264 lesions with APC resulted in a recurrence rate of only 4.5% [22]. The two studies in our meta-analysis that compared STSC with standard EMR reported similar results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In order to reduce recurrence rates, APC is applied to the entire margin of the resection site leaving a white touch indicating the coagulated tissue. In line with our findings, a large retrospective multicenter cohort study from 2019 treating 264 lesions with APC resulted in a recurrence rate of only 4.5% [22]. The two studies in our meta-analysis that compared STSC with standard EMR reported similar results.…”
Section: Discussionsupporting
confidence: 90%
“…And last, alternative strategies not targeting the resection margin were not included in this meta-analysis. These techniques are based on enhancing optical imaging during the EMR and therefore theoretically reduce adenoma recurrence rates, such as underwater EMR [ 12 , 30 ], cap-assisted EMR [ 22 , 31 ], and wide-field EMR [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…distinction between en bloc and piecemeal resection [6,21,25], and only one of these three performed post-hoc analysis to evaluate the specific effects of EMR-T after en bloc and piecemeal resection separately [6]. In this study, there was no significant difference in recurrence rate after traditional en bloc EMR (0/23; 0%) compared to en bloc EMR-T (1/25; 4%).…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…For STSC, universally, the soft coagulation mode is used with a current of 80 Watts and effect mode 4 on Erbe ENDO CUT Q [6,15,[21][22][23]. Settings for APC show more variation between operators, with currents between 30-70 Watts and a gasflow of 0.8-2.0 liters per min [18,19,24,25]. A recent study in porcine models evaluating the effects of STSC and APC showed that APC applied at 1.0 L/min, 30 W, was associated islands of preserved mucosa [26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Hence, our data suggest that special measures should be considered to help ensure that elderly patients undergo follow-up after EMR. Recent breakthroughs in EMR technique, [19][20][21][22] such as application of snare tip soft coagulation thermal injury to the margin of the EMR defect, should result in lower recurrence rates and reduce the implications of lower follow-up rates after EMR in elderly patients. Rates of synchronous disease were similar to younger patients with large sessile or flat colorectal lesions and high in both groups (18).…”
Section: Discussionmentioning
confidence: 99%